Prevalence, characteristics, and associated risk factors of plantar heel pain in americans : The cross-sectional NHANES study - Peng Liu; Qiang Chen; Kun Yang; Fei Cai (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Summary By analyzing data from NHANES, we aimed to evaluate the prevalence, characteristics, and associated factors of plantar heel pain in Americans aged 20 or above. Introduction Plantar heel pain is a prevalent problem that affects a substantial number of adults and significantly impairing their quality of life. Objective To investigate the prevalence and characteristics of plantar heel pain, exploring the associated risk factors. Methods This is a cross-sectional study. We analyzed data from 4957 individuals aged 20 or above who participated in the 2009–2010 NHANES. Results Among the total 4957 US participants ≥ 20 years of age, 549 (11.1%) participants reported plantar heel pain. There was a significant difference in distribution between female and male (p = 0.002). Furthermore, participants aged between 50 and 65 years had the highest plantar heel pain prevalence of 14.5% among the entire population, however, among the female participants, those aged ≥ 65 years demonstrated the highest prevalence (19.8%) of plantar heel pain. In addition, compared to those with BMI < 25 kg/m2, BMI with 25–30 kg/m2 had 1.5-fold risk of plantar heel pain(OR:1.50, 95%CI:1.10–2.05), while BMI with 30–35 kg/m2 had a 2.1-fold higher risk and those with BMI ≧ 35 kg/m2 had a 2.7-fold risk to experience plantar heel pain. Age, BMI, female (OR:1.35, 95%CI:1.07–1.70), kidney stones history (OR:1.52, 95%CI:1.09–2.11), hypertension (OR:1.54, 95%CI:1.20–1.96) and osteoporosis (OR:1.75, 95%CI:1.10–2.78) were independent risk factors for plantar heel pain. Further subgroup analysis indicated that osteoporosis is the independent risk factor for women (OR:2.00, 95%CI:1.19–3.37) but not men (OR:0.65, 95%CI:0.15–2.86) for plantar heel pain. Conclusion Our findings might offer evidences for the prevention and treatment of plantar heel pain. Further prospective studies are needed to confirm our findings.